Ab Initio Study on the Vibrational and Electronic Properties of Radiation-Induced Defects in Potassium Bromide - Platonenko, Alexander; Pankratov, Vladimir; Kotomin, Eugene A.; Dauletbekova, Alma; Popov, Anatoli I. (MDPI, 2024)
The vibrational and electronic properties of several basic radiation defects in potassium bromide are computed at the quantum mechanical level using a periodic supercell approach based on hybrid functionals, an all-electron Gaussian-type basis set, and the Crystalcomputer code. The exciton energy in alkali halides is sufficient to create lattice defects, such as F–H Frenkel defect pairs, resulting in a relatively high concentration of single defects and their complexes. Here, we consider eight defects: the electronic F+ - and F-centers (bromine vacancy without and with trapped electrons) and their dimers; hole H-center (neutral bromine atom forming the dumbbell ion with a regular Br− ion.); V𝐾-center (Br−2 molecular ion consisting of a hole and two regular ions); and two complex Br−3 defects, combinations of several simple defects. The local geometry and the charge- and spin-density distributions of all defects are analyzed. Every defect shows its characteristic features in Raman spectra, and their comparison with available experimental data is discussed. --//-- This is an open-access article: Platonenko, A.; Pankratov, V.; Kotomin, E.A.; Dauletbekova, A.; Popov, A.I. Ab Initio Study on the Vibrational and Electronic Properties of Radiation-Induced Defects in Potassium Bromide. Crystals 2024, 14, 161. https://doi.org/10.3390/cryst14020161 published under the CC BY 4.0 licence,
A.I.P. and A.P. are thankful for the financial support provided by the Latvian Research Council, Grant No. LZP-2018/1-0214. The work of EK was performed in the framework of EUROfusion Consortium, funded by the European Union via the Euratom Research and Training Programme (Grant Agreement No 101052200—EUROfusion). Views and opinions expressed are however those of the author (s) only and do not necessarily reflect those of the European Union or the European Commission. Neither the European Union nor the European Commission can be held responsible for them. This research was conducted at the Center of Excellence of the Institute of Solid State Physics, University of Latvia, and supported through the Framework Program for European Union Horizon 2020, H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; alkali halides; KBr; interstitial defects; F-type centers; hole centers; electronic structure; vibrational properties; Raman spectroscopy